2017
DOI: 10.1515/agri-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic-Matter in Water-Stable Aggregates Under Different Soil-Management Practices

Abstract: An experiment of different management practices in a commercial vineyard, which was established in 2006 in the locality of Nitra-Dražovce, Slovakia on Rendzic Leptosol, was used to evaluate the dynamics of soil organic-matter parameters during the years 2008–2015. The following treatments were established: 1. G (grass without fertilisation as control), 2. T (tillage), 3. T+FYM (tillage + farmyard manure), 4. G+NPK3 (grass + 3rd intensity of fertilisation for vineyards: it means 125 kg/ha N, 50 kg/ha P, 185 kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…4c]. Simansky et al, (2017) reported that the soilmanagement practices significantly influenced the soil organic carbon in water-stable aggregates (SOC in WSA). The content of SOC in WSA ma increased on average in the following order: T<G< G+NPK 1 <G+NPK 3 < T+FYM.…”
Section: Inorganic Soil Carbonmentioning
confidence: 99%
“…4c]. Simansky et al, (2017) reported that the soilmanagement practices significantly influenced the soil organic carbon in water-stable aggregates (SOC in WSA). The content of SOC in WSA ma increased on average in the following order: T<G< G+NPK 1 <G+NPK 3 < T+FYM.…”
Section: Inorganic Soil Carbonmentioning
confidence: 99%
“…It is considered as a eutrophic bacterium and has a positive correlation with the content of total nitrogen and alkali hydrolyzed nitrogen in soil, which plays an important role in soil nitrogen cycle (Fei et al., 2020; Wang et al., 2009). From the genus level of soil rhizosphere bacteria, the relative abundance of anaerobes in GM 2 , GM 3 , and GM 6 with organic fertilizer was significantly lower than that in CF and CK, which might have result from the different partitioning pattern of photoassimilates as shown in Table 6 and also could be the reason that organic fertilizer could promote the formation of soil water stable aggregates and increase the proportion of large aggregates in soil (Šimanský et al., 2017). Therefore, we suggested that the proper application of organic fertilizer optimized the partitioning pattern of photoassimilates in crop plants and rhizosphere soil, especially reducing the allocation of photoassimilates to rhizosphere soil, which was beneficial in decreasing the greenhouse gas emission and the activation of rhizosphere nutrient environment (Lin et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of tillage on SOC and concentration of nutrients in soil aggregates can differ spatially and temporally, depending on various types of soil and crops involved. According to Šimanský et al, [70], soil-management practices significantly affect SOC in water-stable aggregates (WSA). The SOC content in WSA enhanced in the following order i.e.…”
Section: Distribution Of Organic Carbon In Various Aggregate Sizes Af...mentioning
confidence: 99%